SUBJECTIVE WELL-BEING (SWB) AS A DETERMINANT OF RURAL SPA TOURISM DEVELOPMENT: ECONOMIC AND ENTREPRENEURIAL PERSPECTIVES - Cico, Snežana; Ivanović, Tatjana; Gavrilović, Marija (Economics of Agriculture, 2025)
Rural spa tourism represents a vital segment of the rural economy, combining health, recreation, and entrepreneurship within natural environments. This study explores the economic relevance of Subjective Well-Being (SWB) as a determinant of rural spa tourism development. Data were collected from 713 foreign visitors across four rural spa destinations in Central and Southeastern Europe. The analysis integrates economic, psychological, and managerial dimensions, examining how perceived well-being affects visitors’ spending, length of stay, and support for local entrepreneurship. Results reveal that higher levels of SWB are positively associated with greater consumption of wellness services, stronger loyalty intentions, and higher appreciation of local resources. Moreover, visitors reporting higher well-being tend to support small-scale rural businesses and locally sourced products, strengthening the socio-economic resilience of spa destinations. These findings suggest that SWB functions as both a personal recovery indicator and an economic stimulus, reinforcing the link between wellness experiences and sustainable rural development. The study contributes to understanding the role of well-being economics in tourism policy and destination management.